Key elements to encourage research in universities, in the bicentennial of Peru - Bullón Solís, Omar (2021)
The article presents four elements that are considered relevant for promoting research at universities, without claiming to be the only ones. The first is to develop research skills and then to foster collaborative networks teams; second, the strengthening of the leadership of research centers in universities; third, the use of ICTs in the development and distribution of research; the fourth, the promotion of ethics and values in research activity. It is suggested that these elements should be combined with the institutional policies in force in universities and institutions linked to research. These policies acquire a key role in the promotion of research, which is why this analysis is presented to commemorate the bicentennial of the independence of Peru.